2016
DOI: 10.15171/rdme.2016.010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Small Group Discussion in Residency Education Versus Conventional Education

Abstract: Introduction: There are various methods of training for medical students in different colleges. Fast knowledge transfer and maximum learning are the main goals of education. Due to the limited time and also high volume of content knowledge during residency, using the best methods of training can play an important role in enhancing the skills of residents. In the current study, small group discussion as a teaching method was compared with the traditional method. Methods: In this cohort study, two groups of resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
2
0
2
Order By: Relevance
“…The State board exams were compared at end of 4 years of residency program, which showed that the students trained in small groups were significantly more successful in both written and OSCE tests. (15) This performance based comparison is also done in the present study, which shows the objective benefit in success rates and marks obtained by the students in the examination after exposing them to 2 different modalities of teaching.…”
Section: Discussionmentioning
confidence: 61%
“…The State board exams were compared at end of 4 years of residency program, which showed that the students trained in small groups were significantly more successful in both written and OSCE tests. (15) This performance based comparison is also done in the present study, which shows the objective benefit in success rates and marks obtained by the students in the examination after exposing them to 2 different modalities of teaching.…”
Section: Discussionmentioning
confidence: 61%
“…Small groups have improved students 'communication and interaction skills (Annamalay: 2015) [18] The success of small group discussion results of Antoni's research shows that thelearning method small groupanalyzed can improve students' speaking skills. This method can also increase interaction between teachers and students, (Rivi Antoni, 2014) [19] The results of Ali Tabrizi's study, which shows that themethod small group discussion can improve learning skills more effectively than traditional methods,( Ali Tabrizi, 2015) [20].…”
Section: Discussionmentioning
confidence: 99%
“…Berbagai alasan diantaranya adalah menuntut keaktifan peserta dalam diskusi, peningkatan proses berpikir, retensi informasi yang tinggi, dan keterampilan berkomunikasi. [24][25] Penelitian Mualifah juga mendapati hal yang sama yaitu metode diskusi lebih efektif dibandingkan dengan ceramah dalam meningkatkan pengetahuan dan sikap pra remaja menghadapi menarche yang diukur pada hari pertama, ketiga dan keempat belas setelah pendidikan kesehatan. 26 Namun, pada penelitian tersebut tidak menggunakan media intervensi seperti terdapat pada penelitian ini.…”
Section: Faktor Pendukung Dan Penghambat Pelaksanaan Intervensiunclassified